Impact of Digital Technologies, Modern Infrastructure, Self-Service Learning Experience, and Customer Satisfaction at Haidilao Restaurant in China - Lei Biao; Nuttawut Rojniruttikul (My University, 2023)
This study investigated the impact of digital technologies and modern infrastructure on customer satisfaction and self-learning experience among customers of Haidilao Restaurant in China. The study found that customers reported high levels of satisfaction, self-learning experience, digital technologies, and modern infrastructure. The results indicated that digital technologies had a significant negative impact on the self-learning experience but did not significantly impact customer satisfaction. In contrast, modern infrastructure was found to have a significant positive impact on both the self-learning experience and customer satisfaction. Recent literature supports these findings, which suggest that maintaining and improving modern infrastructure can positively influence customers' perceptions and ultimately increase their satisfaction levels. The study contributes to the understanding of the role of digital technologies and modern infrastructure in enhancing customers' experiences in the restaurant industry.
Keywords: Digital Marketing and Social Media; Technology Adoption and User Behaviour; Customer Service Quality and Loyalty